Productivity of Lembah Palu local shallot (Allium cepa L. var. Aggregatum) from organic cultivation - Lapanjang, Iskandar; Amirudin (Penerbit Universiti Kebangsaan Malaysia, 2023)
The local shallot variety of ‘Lembah Palu’ (Allium cepa L. var. Aggregatum) is a typical fried shallot plant in Palu City, Indonesia, and is a cooking spice or flavoring for various foods. The main objective of this research was to increase the productivity of the Palu local shallot of ‘Lembah Palu’ grown on liquefaction soils. This research was conducted from November 2019 to January 2020, in Kaleke Village, West Dolo Subdistrict, Sigi Regency, Central Sulawesi, Indonesia. This research used a Randomized Block Design with two factors. The first factor ofArbuscular Mycorrhiza Fungi (AMF) consisted of M0 (Control), M1 (10 g/polybag), M2 (15 g/polybag), and M3 (20 g/polybag). The second factor of bokashi fertilizer consisted of B0 (Control), B1 (312.5 g/polybag), and B2 (375 g/polybag). Each experimental unit consisted of 3 polybags and was grouped into 3 groups so that the total experimental unit was 108 plants or polybags. The results showed that the application of mycorrhiza 20 g/polybag and bokashi 375 g/polybag was able to produce the optimal number of tubers, the wet and dry weight of shallot tubers. Likewise, for the growth of Palu local shallot plants, the higher dose of mycorrhiza and bokashi resulted in better plant growth, i.e., plant height, number of leaves, and number of tillers.